Dampak Kebijakan Modal Kerja, Leverage, Dan Aset Perusahaan Terhadap Profitabilitas Perusahaan Yang Terdaftar Di Bursa Efek In indonesia Periode 2010-2012 - Agus Zainul Arifin; Prayogo Indrayang (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The objective of this study was to determine the relationship between a working capital policy with proxy Cash Conversion Cycle (CCC), Leverage, company size, and Financial Assets, as independentvariables, and profitability as the dependent variable on the non-financial companies listed in Indonesia Stock Exchange period 2010-2012. To examine this relationship, using panel data regression. Sampling method was non-probability sampling with a purposive sampling technique. The results of the analysis of the evidence obtained in the form of the regression model used are Random effects. The partial test effect proves that the policy of working capital, leverage, asset size, and Financial Assets has no effect on profitability. The test results together prove a significant effect.